DIVERSITY AND CONSERVATION STATUS OF FLORA IN PILAVAKKAL DAM FOOTHILLS OF WESTERN GHATS, TAMIL NADU, INDIA - Gurusamy, Manikandan; Subramanian, Vairamuthu; Raju, Ramasubbu (Association of Indonesian Forestry and Environment Researchers and Technicians, 2022)
The floristic study is necessary to understand the present diversity status and conservation of forest biodiversity. It has been realized that the study of local or regional flora is of much more significance than those covering big areas because explorations can be carried out intensively in small areas with damaging consequences. Understanding species diversity and distribution patterns are important to evaluate the complexity and resources of these forests. In the present study, the medicinal floristic diversity of Pilavakkal dam Foothills of the Western Ghats comprised of 127 species belonging to 42 families and 100 genera. Fabaceae, Malvaceae and Lamiaceae were dominant families with 23, 11 and 10 species, respectively. The total number of species includes 55 herbs, 23 shrubs, 37 trees and 12 climbers. Totally 127 important medicinal plant species are recorded in Pilavakkal dam Foot Slopes of Western Ghats. Psydrax dicoccos is vulnerable in this list, 27 plants species are Least Concern and Mangifera indica comes under the Data Deficient and 98 plants species evaluated are not categorized by IUCN. This study provides basic information about the medicinal flora and conservation status of the Pilavakkal dam Foothills of Western Ghats. It would also be helpful for the identification of flora and to derive conservation policies and make sustainable use of plant resources